AN ANALYSIS OF REPRESENTATIVE IN DONALD TRUMP’S IMPEACHMENT CAMPAIGN - Eny Akwila Neonbanu (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
This research is an analysis of representative in Donal Trump’s impeachment campaign. The aim of this reasearch is to know how Donal Trump applied representative to persuade the hearers. How a speech of Donal Trump could affect the audience to do something for him to win the second election. In this study, the researcher used qualitative method, and the data were collected from a speech text. The transcript speech text of Donal Trump’s utterances consisting of representative was the instrument of this research. Then, to find and analyze the representative showed in the text speech, the researcher used a theory of John R. Searle (1969) which explains that representative is one of the illocutionary acts that the utterance with the intention to commit the speaker to do something with the truth of expressed proposition. The representatives found in this research were, 1 representative of stating, 3 representatives of informing, 1 representative of predicting, 1 representative of reporting, 1 representative of describing, 1 representative of complaining, 1 representative of claiming, and 2 representatives of asserting. In this study showed that Donal Trump succeed inciting the hearers making a riot to the capitol by believeing in his statements on his impeachment campaign. How his utterances were manipulative and making the audience agreed to the statements he said. The researcher hopes that this analysis would be useful who would like to learn about speech act and illocutionary act, especially about representative illocutionary act.